2012
DOI: 10.1063/1.4754549
|View full text |Cite
|
Sign up to set email alerts
|

The thickness and stretch dependence of the electrical breakdown strength of an acrylic dielectric elastomer

Abstract: The performance of dielectric elastomer actuators is limited by electrical breakdown. Attempts to measure this are confounded by the voltage-induced thinning of the elastomer. A test configuration is introduced that avoids this problem: A thin sheet of elastomer is stretched, crossed-wire electrodes are attached, and then embedded in a stiff polymer. The applied electric field at breakdown, EB, is found to depend on both the deformed thickness, h, and the stretch applied, λ. For the acrylic elastomer investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
88
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 143 publications
(95 citation statements)
references
References 32 publications
6
88
1
Order By: Relevance
“…2(b)). A three-fold change in E B has been observed over the investigated parameter range of h and k. The breakdown field strength exhibits a clear trend for samples with the same initial thickness H, which implies that the dielectric breakdown field strength depends on both thickness and stretch simultaneously, as found by Huang et al 18 for the VHB 4910 polyacrylate elastomer. All the data at different thicknesses h and stretch ratios k collapse onto a single line (Fig.…”
supporting
confidence: 57%
See 1 more Smart Citation
“…2(b)). A three-fold change in E B has been observed over the investigated parameter range of h and k. The breakdown field strength exhibits a clear trend for samples with the same initial thickness H, which implies that the dielectric breakdown field strength depends on both thickness and stretch simultaneously, as found by Huang et al 18 for the VHB 4910 polyacrylate elastomer. All the data at different thicknesses h and stretch ratios k collapse onto a single line (Fig.…”
supporting
confidence: 57%
“…[1][2][3][4][5][6][7][8] The dielectric breakdown strength is the ultimate physical limit that hinders the possibility of actively stretching a dielectric elastomer up to its mechanical failure and, therefore, is of paramount importance in defining the actuator performance bounds. 4,9 It does not depend solely on the chemical properties of the material, but also on its physical properties such as mechanical stiffness, 10,11 thickness, [12][13][14][15][16][17] and stretch state, [18][19][20] the latter of great interest for dielectric elastomer actuators (DEAs) due to its beneficial effects on actuation. 4,9,20,21 In literature, the combined effect of thickness and pre-stretch on the breakdown strength of soft elastomers eligible to be used as actuators has been studied mostly for the acrylic elastomer VHB 4910, widely used for early implementations of dielectric elastomer actuators, thanks to its commercial availability as a bonding tape.…”
mentioning
confidence: 99%
“…It is well known that the electrical breakdown performance of dielectric elastomers is influenced strongly by material conditions such as the Young's modulus, 21 applied pre-strain 20,22-24 and elastomer thickness. 22,24 Electrical breakdown strength values remain constant within experimental uncertainty, irrespective of the concentration of the added ionic network, the presence of which in the investigated concentrations therefore does not affect the overall breakdown strength of the materials.…”
Section: Self-healing High-permittivity Silicone Dielectric Elastomermentioning
confidence: 99%
“…Previous experiments have shown that the electric breakdown of dielectric elastomer may depend on the sample thickness and prestretch. [34][35][36] For simplicity, here we assume that E failure is constant. 24 Specifically, E failure is chosen as 50 MV/m.…”
mentioning
confidence: 99%
“…24 Specifically, E failure is chosen as 50 MV/m. 35,36 Figure 5 plots the failure point of dielectric composite. For elastomer with fiber mainly distributed in the dominate direction (b = 50), the materials suffer pull-in instability.…”
mentioning
confidence: 99%